Adverse Effects of Polycystic Ovarian Syndrome on Pregnancy Outcomes in Women With Frozen-Thawed Embryo Transfer: Propensity Score-Matched Study - Ni, Zhexin; Mei, Shanshan; You, Siting; Lin, Yi; Cheng, Wen; Zhou, Ling; Kuang, Yanping; Yu, Chaoqin (Frontiers in Endocrinology, 2022)
Purpose To evaluate the adverse effect of polycystic ovary syndrome (PCOS) on pregnancy outcomes after vitrification in women with frozen-thawed embryo transfer. Methods Patients with/without PCOS after frozen-thawed embryo transfer (FET) from January 2013 and December 2018 were included. Propensity score matching (PSM) was used to reduce the influence of bias. Logistic regression was applied to identify the risk factors of adverse pregnancy outcomes in women with PCOS. Result After PSM, the gestational age was shorter (P<0.001) and the birth weight of a newborn in the PCOS group was less than the non-PCOS group (P=0.045). Compared to the non-PCOS group, the PCOS group had an increased risk of pregnancy complication (P<0.001), placenta and membrane abnormality (P<0.001), stillbirth (P<0.001), neonatal complication (P=0.014) and miscarriage rate (P<0.001). The neonatal complication was associated with parity (adjusted OR=1.202, 95% CI=1.002-1.443, P=0.048) and basal P level (adjusted OR=1.211, 95% CI=1.021-1.436, P=0.028). In multivariable logistic regression analysis, the miscarriage rate was related to parity (adjusted OR=1.201, 95% CI=1.057-1.166, P=0.005), basal E2 level (adjusted OR=1.002, 95% CI=1.000-1.004, P=0.019), and the P level on the day of embryo transfer (adjusted OR==0.971, 95% CI=0.957-0.985, P<0.001). Conclusions Compared to non-PCOS women, Women with PCOS demonstrate a higher risk of pregnancy complications and neonatal complications. Women with these risk factors need to be paid more care during pregnancy and parturition.